Differences in the Incidence of Urinary Retention in Spinal Anesthesia Between Lidocaine 2% 60mg and Buvipacaine 0.5% 10 Mg in Postoperative Patients at RS PKU Muhammadiyah Gamping - Nurcartenzia, Reinascita; Setiawan, Yosy Budi (Jurnal Health Sains, 2025)
The most common regional anesthesia procedure used in various operations, especially operations on the lower abdomen and lower extremities, is spinal anesthesia. Urinary retention is a urination disorder, where the flow of urine is weak, not flowing smoothly, and there is a feeling of something remaining and dissatisfaction when urinating, resulting in discomfort. Urinary retention is one of the common complications that occurs after spinal anesthesia. This study aims to determine the comparison of the incidence of urinary retention after spinal anesthesia with lidocaine 2% 60mg and bupivacaine 0.5% 10mg. the test results showed that the p-value = 0.500 (p>0.05), so H1 was rejected and H0 was accepted, which means there is no significant relationship between the incidence of urinary retention and the anesthetic drugs lidocaine or bupivacaine. There is no significant difference regarding the incidence of urinary retention during spinal anesthesia between lidocaine 2% 60 mg and bupivacaine 0.5% 10 mg in postoperative patients at PKU Muhammadiyah Gamping Hospital.